PELAKSANAAN PREGNANCY NURSING TERPADU PADA IBU HAMIL DAN CONTINUITY OF CARE PADA NEONATUS DI KLINIK MADINAH MEDAN: PELAKSANAAN PREGNANCY NURSING TERPADU PADA IBU HAMIL DAN CONTINUITY OF CARE PADA NEONATUS DI KLINIK MADINAH MEDAN - Fika Lestari; Yusnaini; Lubis, Halimatussakdiyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2023)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are still the main problems in Indonesia's health development. AKI or Maternal Mortality Rate (MMR) is an indicator of women's health level that describes the level of access, integrity, and effectiveness of the health sector. Therefore MMR is used as an indicator of the level of welfare of a country. Ministry of Health, 2015). The goal of midwifery services for pregnant women is to get integrated and comprehensive services according to standards, should make at least six visits during the antenatal period, namely one visit during the first trimester, once during the second trimester, and twice during the third trimester, as well as two visits to specialists. pregnancy in the first and third trimesters. It is necessary to immediately check the pregnancy if there is a disturbance or if the fetus does not move for more than 12 hours (Rachman, 2021). Efforts made by the government to reduce IMR include: (a) improving Neonatal health services, namely by requiring that every newborn receive Neonatal Visit services at least 3 times (KN1, KN2, and KN3) according to standards. (b) Neonatal care with abnormalities or complications/emergencies according to health worker standards where services include Integrated Management of Young Babies (MTBM), Management of Newborn Asphyxia, and Management of Low Birth Weight Babies (Ministry of Health, 2015). Implementation of Integrated Pregnancy Nursing for Pregnant Women and Continuity Of Care for Neonates at the Medina Clinic Medan involving pregnant women and mothers with babies aged 0-28 days with a total of 20 people January 16-February 16 2023 at the Medina Clinic Jalan Datuk Kabu Pasar 3 Tembung, integrated pregnancy nursing activities for pregnant women are carried out in stages. The stages carried out include screening pregnant women with cadres. Then it is planned for the final examination of pregnant women to provide health education on the problems found. Furthermore, continuity of care activities when the baby is 6-48 hours old (KN 1), 3-7 days (KN II), and 8-28 (KN III). Providing care during neonatal visits is carried out to monitor growth, and development, monitor the fulfillment of asah, compassion, and care needs, and monitor danger signs